Diagnostics of Oil Filled Cable Terminations - Mohd Rafi, Adzman; Muzamir, Isa; Baharuddin, Ismail; Lehtonen, Matti; Hyvonen, Petri (Kolej Universiti Kejuruteraan Utara Malaysia, 2008)
Link to publisher's homepage at http://jere.unimap.edu.my